The Relationship Between Smartphone Addiction and Attention Among Medical Students at Atma Jaya Catholic University of Indonesia - Amelia Prasetyadi; Lenny Gustaman (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2022)
Introduction: Smartphone addiction is characterized by a strong attachment to the smartphone that allows the occurrence of social problems and difficulty in performing everyday activities. Cognitive function disruption is one of smartphone addiction’s negative effects, and one component of cognitive function is attention. The prevalence of smartphone addiction in adolescents and young adults was higher since they were relatively more familiar to technology and lacked self-control. The purpose of this study is to determine the relationship between smartphone addiction and attention among medical students at Atma Jaya Catholic University of Indonesia. Methods: An analytical, cross-sectional study was conducted with a total of 82 respondents. The respondents were from the 2016, 2017, and 2018 batch of medical students at Atma Jaya Catholic University of Indonesia and were selected by stratified random sampling. The data were gathered using Smartphone Addiction Scale Short Version (SAS-SV) questionnaire, in order to estimate the prevalence of smartphone addiction and the Stroop Test to measure attention. Results. The majority of the subject were female (70,7%) and aged around 17-21 years. The respondents who were addicted to smartphones were 48,8%, and most respondents who were addicted were using their smartphone for 5-≤7 hours/day (63,3%) and spent their time more on social media (56,7%). The mean attention score was 63,81. The mean attention score for non-smartphone addicts was higher than the addicted ones, but there is no statistically significant correlation between smartphone addiction and attention (p= 0,06). Conclusions. There is no significant correlation between smartphone addiction and attention.